Aplikasi Metode Magnetotelurik Dalam Interpretasi Struktur Panas Bumi: Daerah Panas Bumi Gunung Karua, Tana Toraja Sulawesi Selatan - Zarkasyi, Ahmad; Syaifuddin, Firman; Setiawan, Nugroho Syarif (Jurnal Geosaintek, 2019)
Bittuang Geothermal area has manifestations consisting of hot springs and alterations rock with reservoir temperature estimated about 200°C. The previous research and field observations lead us to carry out continuing research in this area, which is aimed at determining its resistivity structure to a depth about 2-4 km. This paper demonstrates the utilization of two -dimensional (2D) magnetotelluric (MT) inversions, which leads to characterizing the electrical resistivity structure of geothermal reservoirs. For this purpose, we carried out field measurements using Magnetotelluric (MT) methods. The study results reveal the existence of a strike as indicated from the geological data and a low resistivity zone at a shallow surface to a depth about 1-1.25 km that is most probably associated with alteration rock or claycap. The zone below the claycap with higher resistivity (50-250 ohmm) is indicated as reservoir zone.